1995
DOI: 10.1099/00222615-42-5-362
|View full text |Cite
|
Sign up to set email alerts
|

Post-antibiotic effect of azithromycin and erythromycin on streptococcal susceptibility to phagocytosis

Abstract: Summary. The effect of azithromycin and erythromycin on growth, cell surface hydrophobicity and the susceptibility to the bactericidal activity of human polymorphonuclear leucocytes (PMNL) was examined in four Streptococcus species. Exposure to either 10 x MIC azithromycin or erythromycin induced a post-antibiotic effect (PAE) of between 2.4 and 4.3 h. Erythromycin caused a longer PAE for S. sanguis than azithromycin under the same conditions. The cell surface charge (hydrophobic or hydrophilic) of the strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…B. pseudomallei is an intracellular pathogen and has been found to be able to resist intracellular killing by phagocytes (13,35). Many studies have demonstrated that subinhibitory concentrations of antibiotics increase the susceptibilities of bacteria to phagocytosis or killing by phagocytes (3,4,27,30). Not only is B. pseudomallei resistant to killing by monocytes, but it also kills monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. pseudomallei is an intracellular pathogen and has been found to be able to resist intracellular killing by phagocytes (13,35). Many studies have demonstrated that subinhibitory concentrations of antibiotics increase the susceptibilities of bacteria to phagocytosis or killing by phagocytes (3,4,27,30). Not only is B. pseudomallei resistant to killing by monocytes, but it also kills monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many have reported on the altered adherence and phagocytosis of antibiotic-induced filaments in other bacteria (3,4,27). Decreased phagocytosis of these filaments was likely due to mechanical constraints.…”
Section: Mics and Mbcs Of Antibioticsmentioning
confidence: 99%
“…The other accompanying effects include changes in cell morphology (Hanberger et al, 1993), inhibition of enzyme and toxin production (Shibl et al, 1994), loss of adhesive properties and reduction of cell-surface hydrophobicity (Shibl et al, 1994;Ramadan et al, 1995), and increased susceptibility to host humoral and cellular immunity (Minguez et al, 1994;Ramadan et al, 1995). Many of these effects are probably overlapping and closely linked.…”
Section: (V) Susceptibility Testingmentioning
confidence: 99%
“…The PAE value of the antibiotic for the isolate was 1 h. In our former experiments the PAE values were significantly different for other species of streptococci -3.4 and 3.5 h for the S. anginosus strains 2 and 2,8 h for the group A streptococcus 15,16 . RAMADAN et al 35 reported that erythromycin and azythromycin induced PAE against group A streptococci -2.4 and 4.3 h respectively -and several other studies have assessed the PAE of antimicrobials on Gram-positive cocci.…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation we also observed that treatment of group A streptococci with penicillin did not influence the cell-surface hydrophobicity as the magnitude of changes in value of angles did not differ significantly 15 . RAMADAN et al 35 showed a decrease of the group A streptococcal cell-surface hydrophobicity during the PAE induced by azythromycin and erythromycin. The alterations could be related to mechanisms such as effects on the bacterial surface, formation of aberrant adhesins, suppression of production of surface adhesins or even absence of expression of these adhesions 1,24.37,41 .…”
Section: Discussionmentioning
confidence: 99%